Miopia Ringan Pada Anak - Zenith Puspitawati; Putu Ristyaning Ayu; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Myopia is a serious health problem because its prevalence continues to increase worldwide. Myopia is a condition in which incoming light falls in front of the retina, causing blurred vision when looking at distant objects. In 2050 it is predicted that at least 49.8% of the world's population will suffer from high myopia of 9.8%. In children, refractive disorders, such as myopia, are often associated with vision care factors, however, several studies suggest that other factors have a significant relationship with the occurrence of myopia, namely genetic, environmental, gender, sleep duration, and economic status. This study aims to get an overview of mild myopia in children. The type of research is a literature review obtained from Text Books, Google Search, and Google Scholar. Found 7 literature. The results of the study found that there was no significant relationship between genetic variables and existing myopia. However, in another study, children with myopia parents had a higher prevalence of myopia. Factors that have a relationship with the incidence of myopia are environmental factors.